The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/bf03215553
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of selective CO oxidation on nanosized Auγ-Al2O3 catalysts

Abstract: Nanometer-sized gold particles on oxide supports are efficient catalysts for the selective catalytic oxidation (SCO) of carbon monoxide under conditions compatible with the operation of PEM fuel cells. Nanosized Au/␥-Al 2 O 3 catalysts are able to oxidize CO between 20 and 70°C in an atmosphere of hydrogen combining high CO conversion and satisfactory selectivity to CO 2 (1). It is generally agreed that the catalytic activity of gold depends on the size of the gold particles, but the nature of support material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Similar results were obtained for the other analysed samples (images not shown). Other authors also found gold in the reduced state in doped alumina materials, as reported in the literature (Grisel et al 2000(Grisel et al , 2001(Grisel et al , 2002aGrisel and Nieuwenhuys 2001a, b;Gluhoi et al 2003Gluhoi et al , 2004Gluhoi et al , 2005aGluhoi et al , b, 2006aLin et al 2004;Gavril et al 2006;Gluhoi and Nieuwenhuys 2007a, b;Lippits et al 2007Lippits et al , 2008Lippits et al , 2009). …”
Section: X-ray Photoelectron Spectroscopysupporting
confidence: 56%
“…Similar results were obtained for the other analysed samples (images not shown). Other authors also found gold in the reduced state in doped alumina materials, as reported in the literature (Grisel et al 2000(Grisel et al , 2001(Grisel et al , 2002aGrisel and Nieuwenhuys 2001a, b;Gluhoi et al 2003Gluhoi et al , 2004Gluhoi et al , 2005aGluhoi et al , b, 2006aLin et al 2004;Gavril et al 2006;Gluhoi and Nieuwenhuys 2007a, b;Lippits et al 2007Lippits et al , 2008Lippits et al , 2009). …”
Section: X-ray Photoelectron Spectroscopysupporting
confidence: 56%
“…However, reconstruction of the gold particles under reaction conditions can not be fully ruled out 33. However, since the amounts of water liberated and hydroxy groups lost directly depended on the specific surface area of the alumina support, and since this reactivity pattern is specific to high‐surface‐area alumina‐supported gold catalysts12 and was not detected in the activity patterns of gold nanoparticles supported on low‐surface‐area alumina,20b the involvement of OH and H 2 O is likely. Conversely, both the titania‐ and zirconia‐supported catalysts were activated under reaction conditions upon heating to 280 °C, despite the likely formation of poisonous surface carbonate species under these conditions 34.…”
Section: Resultsmentioning
confidence: 99%
“…42 The presence of water in the CO+O 2 feed is also known to directly promote the CO oxidation activity of an alumina‐supported gold catalyst, a lot more significantly than that of Au/TiO 2 ,32b potentially by hydroxylation of the high‐surface‐area material. Enhancement in the low‐temperature CO oxidation rate over alumina‐supported gold catalysts in PROX has also been attributed to the weakening of CO adsorption on gold with hydrogen in the feed 12. However, the promotion was maximal only after a whole heating step under PROX conditions, which suggests that there is more than just an effect of H 2 on the gas and adsorbed phases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alumina has been classified as inactive support in contrast to materials like TiO 2 or Fe 2 O 3 , which exhibit oxidative abilities 5 as does CeO 2 29. Nevertheless alumina‐supported gold catalysts show very good catalytic performance 59, 30–32. The interaction of small gold clusters with surface sites of alumina is expected to affect the coordination of the metal atoms in the interface region and eventually the dispersion of supported metal species as larger metal particles form from such smaller adsorbates.…”
Section: Introductionmentioning
confidence: 99%